Risky positioning – social aspirations and risk-taking behaviour in avalanche terrain. Issue 4 (4th July 2021) - Mannberg, Andrea; Hendrikx, Jordy; Johnson, Jerry
ABSTRACT: We test if positionality, i.e., the desire to gain social status, is associated with an increased willingness to take risk among backcountry riders. If positional preferences drive risk-taking behaviour in avalanche terrain, this is especially problematic because the stakes are high and can be fatal. Our analysis is based on data for hypothetical choices from an online survey (N = 648) in North America. We find that positional riders are significantly more likely to boast about riding bold lines, more likely to associate steep riding with social respect, and more likely to say that they would accept to ride a potentially risky line. The positionality effect is present regardless of level of avalanche training. We discuss implications for avalanche training and education.